INTERNAL AUDIT, INTERNAL CONTROLS, AND FISCAL DISCIPLINE: EMPIRICAL INSIGHTS FROM STRENGTHENING CONTROL SYSTEMS AS DRIVERS OF FINANCIAL ACCOUNTABILITY IN NIGERIAN LOCAL GOVERNMENTS - Kolawole, Kayode David (J-MACC : journal of management and accounting, 2024)
The purpose of this study is to examine the effects of internal audit control and internal control systems on financial accountability in Nigerian local governments, based on a case study of Ilorin West, Kwara State. Using agency and stewardship theories as the theoretical base, a quantitative survey design was employed using purposive sampling of 125 accounting and audit staff members, with reliability analysis verifying the strength of the constructs and ordered logit regression empirically validating the hypothesised relationships. The results show that internal audit control and internal control systems have significant and positive effects on financial accountability, with internal control systems having a greater impact. These results emphasise the significance of institutionalised audit mechanisms, preventive controls, and staff commitment in maintaining transparency and fiscal discipline. The policy implications are that strengthening audit independence, strengthening compliance structures, and making use of incentive-compatible measures that combine sanctions with rewards are necessary. The study adds to the accountability and governance literature by illustrating how effective control frameworks enhance local government financial management and reinforce fiscal decentralisation and citizen confidence in public institutions.